Implementation and problems of Applying the Merdeka Curriculum in Arabic Language - Nadiya, Nadiya; Aulia, Puteri; Mulyansyah, Fajar; Noor, Fatwiah (Journal Of Foreign Language Learning and Teaching, 2024)
The curriculum serves as the foundation of education in Indonesia, continually evolving to meet the changing needs of students. The Merdeka Curriculum emerges as a solution to meet these needs. This research aims to identify the problems that arise in the implementation of the Merdeka Curriculum in Arabic language learning and to provide solutions that can enhance the effectiveness of its implementation. This study uses a literature review method to analyze relevant literature in the context of implementing the Merdeka Curriculum in Arabic language learning in Indonesia. Data were obtained from various literature sources, including scientific journals, articles, and research reports. The results show that the Merdeka Curriculum in Arabic language education in Indonesia faces problems due to limited resources, teacher skills, and curriculum adjustments, which can be addressed by improving facilities, enhancing teacher training, integrating technology and active learning, and increasing community involvement.